The Waterlow killings : a portrait of a family tragedy - Burton, Pamela (Melbourne University Publishing, 2012)
Anthony Waterlow left his decrepit, rubbish-filled room in a run-down boarding house at 4.45 pm on Monday 11 November 2009. By 6 pm, the 42-year-old was seen leaving another home: his sister Chloe's in Randwick .He left behind her slaughtered body and that of their father; celebrated art curator Nick Waterlow.